Microbial composition of spiny ants (Hymenoptera: Formicidae: Polyrhachis) across their geographic range - Ramalho, Manuela Oliveira [UNESP]; Bueno, Odair Correa [UNESP]; Moreau, Corrie Saux (Springer Nature, 2017)
Background: Symbiotic relationships between insects and bacteria are found across almost all insect orders, including Hymenoptera. However there are still many remaining questions about these associations including what factors drive host-associated bacterial composition. To better understand the evolutionary significance of this association in nature, further studies addressing a diversity of hosts across locations and evolutionary history are necessary. Ants of the genus Polyrhachis (spiny ants) are distributed across the Old World and exhibit generalist diets and habits. Using Next Generation Sequencing (NGS) and bioinformatics tools, this study explores the microbial community of >80 species of Polyrhachis distributed across the Old World and compares the microbiota of samples and related hosts across different biogeographic locations and in the context of their phylogenetic history. Results: The predominant bacteria across samples were Enterobacteriaceae (Blochmannia - with likely many new strains), followed by Wolbachia (with multiple strains), Lactobacillus, Thiotrichaceae, Acinetobacter, Nocardia, Sodalis, and others. We recovered some exclusive strains of Enterobacteriaceae as specific to some subgenera of Polyrhachis, corroborating the idea of coevolution between host and bacteria for this bacterial group. Our correlation results (partial mantel and mantel tests) found that host phylogeny can influence the overall bacterial community, but that geographic location had no effect. Conclusions: Our work is revealing important aspects of the biology of hosts in structuring the diversity and abundance of these host-associated bacterial communities including the role of host phylogeny and shared evolutionary history.
Keywords: amplicon sequencing; Blochmannia; Lactobacillus; microbes; NGS; Wolbachia